Neutrino phenomenology via Type-(I+II) seesaw in the $U(1)_{L_e-L_μ}$ model - Mishra, Priya; Kumar Behera, Mitesh; Panda, Papia; SINGIRALA, SHIVARAMAKRISHNA; Mohanta, Rukmani (SciPost physics proceedings, 2025)
We show how, L_e-L_μ L e − L μ gauged symmetry is used as the Standard Model (SM) extension with the type (I+II) seesaw mechanism for neutrino mass generation. The particle content of this model involves three extra right handed neutrinos, one scalar triplet and one singlet with the SM spectrum. We discuss about lepton flavour violating decays μ → eγ μ → e γ , τ → μ \bar μμ τ → μ μ ‾ μ and anomalous magnetic moment of muon.